Urine Injury Biomarkers Are Not Associated With Kidney Transplant Failure. Issue 6 (June 2020) - Koyawala, Neel; Reese, Peter P.; Hall, Isaac E.; Jia, Yaqi; Thiessen-Philbrook, Heather R.; Mansour, Sherry G.; Doshi, Mona D.; Akalin, Enver; Bromberg, Jonathan S.; Harhay, Meera N.; Mohan, Sumit; Muthukumar, Thangamani; et al.
Abstract : Background: Kidneys transplanted from deceased donors with serum creatinine-defined acute kidney injury (AKI) have similar allograft survival as non-AKI kidneys but are discarded at a higher rate. Urine injury biomarkers are sensitive markers of structural kidney damage and may more accurately predict graft outcomes. Methods: In the 2010–2013 multicenter Deceased Donor Study of 2430 kidney transplant recipients from 1298 donors, we assessed the association of donor urine injury biomarkers microalbumin, neutrophil gelatinase-associated lipocalin, kidney injury molecule-1, IL-18, and liver-type fatty acid binding protein with graft failure (GF) and death-censored GF (dcGF) using Cox proportional hazard models (median follow-up 4 y). We examined if serum creatinine-defined donor AKI modified this association to assess the relationship between subclinical donor AKI (elevated biomarkers without creatinine-defined AKI) and GF. Through chart review of a subcohort (1137 recipients), we determined associations between donor injury biomarkers and a 3-year composite outcome of GF, mortality, or estimated glomerular filtration rate ⩽ 20mL/min/1.73m 2 . Results: Risk of GF, dcGF, and 3-year composite outcome did not vary with donor injury biomarker concentrations after adjusting for donor, transplant, and recipient characteristics (adjusted hazard ratio ranged from 0.96 to 1.01 per log-2 increase in biomarker). Subclinical injury in transplanted kidneys without AKI was not associated with GF. Conclusions: AKI measured using injury biomarkers was not associated with posttransplant graft outcomes (at median 4 y posttransplant). When assessing posttransplant graft viability, clinicians can prioritize other donor and recipient factors over donor kidney injury, measured by either serum creatinine or urine injury biomarkers. Abstract : Supplemental Digital Content is available in the text.